Dynamic capabilities in strategy formation and knowledge conversion in Zimbabwean organisations - Kagondo, Brian Victor Tinashe (University of the Witwatersrand, Johannesburg, 2023)
This qualitative research study adopts a Strategy-As-Practice approach to theorise organisational strategy formation and knowledge conversion processes. Using the theoretical lenses of Contingency Theory and Institution-, Resource- and Knowledge- based views, the study explores the dynamics of the interactions between organisation systems and people activities in strategy formation. The research context is Zimbabwe, a developing country with high literacy levels but has traditionally been marred by poor institutions and high levels of regulation. The research adopted a generic qualitative research design with triangulated interviews, documents, and a review of records. Data was collected from 13 participants using semi-structured interviews. The participants were senior management and employee representatives who were purposively selected from large organisations from each agriculture and tourism sector, two industry institutions, and one consultant from each sector. This was supplemented with data from documents, records, and minutes of strategy meetings and organisational processes. The findings suggested that: a) While the strategy formation process is formalised, structured and well recorded, the praxis is instead to follow the expectations of tradition and of stakeholders, which produces aesthetically compliant blueprints which are archived; b) Organisations abide by tenets of Contingency Theory in their wish to establish the best fit between internal and external environments. However, they tend to achieve the fit through random and often chaotic systems that feed off the tacit capabilities of individuals or views of managers in positions of power and authority; c) While managers enlist strategy consultants, ‘politically correct’ institutions and specialist technical advisors in sensing the environment, it is the firm owners that direct the seizing and configuration decisions and determine the ideal culture and strategies; d) Tacit knowledge among shop-floor employees is a key but poorly tapped intelligence source, as management elects to preserve the privilege of strategising. Brian V T Kagondo, Stud No. 1316671, PhD Thesis - WBS Page | iii The study concluded that due to an overriding desire for perceived political and procedural correctness, there is fractured and inconsistent understanding and interpretation of the strategy formation processes and strategic outcomes. Strategy- making in Zimbabwe is not absolutely defined and, therefore, is positioned between deliberate and emergent. Organisations navigate the context through turbid harnessing of internal social dynamics, individuals’ tacit knowledge and a broader range of stakeholders. The study makes two theoretical contributions. In the Knowledge-Based View, the study proposes a review of the assumptions to include that tacit knowledge in its pure form is intrinsic and unshareable. Therefore, individuals may only transfer and share those skills they have conscious control of and voluntarily wish to impart to others. To the Institution Based View, the study proposes; the isolation and recognition of the owners or founders of organisations as a distinct Institution that falls in a realm between the external and the internal environments of the organisations. These founders or owners (and sometimes through their representatives, the Board of Directors) are not just advisors but are actually definers of the organisation's culture, mission and broader goals. Management are therefore mere implementers of the institutionalised practices. This challenges the traditional theory, definition and role of management to imply that they are not deciders, planners, organisers and controllers but are simply administrators.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg 2023
Keywords: UCTD; practice; praxis; practitioners; process; strategy formation; knowledge conversion; tacit knowledge; strategy-as-practice; contingency theory; knowledge-based view; resource-based view; institution-based view; Zimbabwe; SDG-17: Partnerships for the goals